Blockade of glutamatergic transmission in the primate basolateral amygdala suppresses active behavior without altering social interaction - Forcelli, Patrick A. (Behav Neurosci, 2017)
The amygdala is an integrator of affective processing, and a key component of a network regulating social behavior. While decades of lesion studies in non-human primates have shown alterations in social interactions after amygdala damage, acute manipulations of the amygdala in primates have been under-explored. We recently reported (Wellman, Forcelli, Aguilar, & Malkova, 2016) that acute pharmacological inhibition of the basolateral complex of the amygdala (BLA) or the central nucleus of the amygdala increased affiliative social interactions in experimental dyads of macaques; this was achieved through microninjection of a GABA-A receptor agonist. Prior studies in rodents have shown similar effects achieved by blocking NMDA receptors or AMPA receptors within the BLA. Here, we sought to determine the role of these receptor systems in the primate BLA in the context of social behavior. In familiar dyads, we microinjected the NMDA receptor antagonist AP7 or the AMPA receptor antagonist NBQX and observed behaviors and social interactions in the immediate post-injection period. In striking contrast with our prior report using GABA agonists, and in contrast with prior reports in rodents using glutamate antagonists, we found that neither NMDA or AMPA blockade increase social interaction. Both treatments, however, were associated with decreases in locomotion and manipulation and increases in passive behavior. These data suggest that local blockade of glutamatergic neurotransmission in BLA is not the functional equivalent of local activation of GABAergic signaling, and raise interesting questions regarding the functional microcircuitry of the non-human primate amygdala in the context of social behavior.